1995
DOI: 10.1038/sc.1995.133
|View full text |Cite
|
Sign up to set email alerts
|

Clinical approach to erectile dysfunction in spinal cord injured men. A review of clinical and experimental data

Abstract: Despite the many developments in the area of sexual dysfunction, rehabilitation settings seldom investigate the remaining sexual function following spinal cord injury, or offer differential diagnoses of sexual dysfunction in spinal cord injured men. This article attempts to show how sexual rehabilitation should begin with a thorough assessment of the sexual function of paraplegic and tetraplegic men. Assessment includes a basic neurological examination of the perineal area and an extended clinical interview on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
0
15
0
2
Order By: Relevance
“…31,32 A variety of management options could be adopted for individuals with SCI. 33 However, therapies for ED caused by SCI remain challenging, and PDE5 inhibitors, vacuum devices, penile implants, intraurethral prostaglandins, percutaneous perineal electrostimulation, transdermal nitroglycerin, intracavernous injection of papaverine and some other therapies are still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 A variety of management options could be adopted for individuals with SCI. 33 However, therapies for ED caused by SCI remain challenging, and PDE5 inhibitors, vacuum devices, penile implants, intraurethral prostaglandins, percutaneous perineal electrostimulation, transdermal nitroglycerin, intracavernous injection of papaverine and some other therapies are still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is reported that 80-95% of these patients can achieve some type of erection: reflexogenic, psychogenic or mixed. 3,10 Treatment options for ED in patients with SCI include intracavernosal injection of vasoactive substances, VCD and surgical implantation of penile prothesis. 3,6,8 The American Urological Association Panel on the treatment of organic ED stated that the ultimate goal is a therapy that is reliable, has minimal side effects and is simple to use.…”
Section: Discussionmentioning
confidence: 99%
“…However, these erections are often less rigid and more difficult to maintain. 7,8 In men with complete SCI, more than 80% can achieve an erection, whether reflexogenic, psychogenic, or mixed; however, most of these patients require some type of treatment for ED. In men with incomplete SCI, the response varies.…”
Section: Pathophysiologymentioning
confidence: 99%